Profil Sadar Bencana Pengunjung Kawasan Wisata Rawan Bencana Gunung Merapi di Kabupaten Sleman, DIY - Budiatiningsih, Mahmudah; Rosyidie, Arief (JURNAL MASTER PARIWISATA; Volume 09, Nomor 01, Juli 2022, 2022)
The tourism sector in the disaster-prone area of Mount Merapi continues to increase and has become one of the main sources of income for the local community after the major eruption of Mount Merapi in 2010. The high number of visitors with various characteristics to disaster-prone areas has placed visitors at high risk during a disaster, especially those with no disaster awareness. Visitors should possess disaster awareness to reduce the risks when a disaster occurs. This study aims to determine the visitors' disaster awareness profile to volcanic eruptions in the disaster-prone area of Mount Merapi. The results indicated that visitors' disaster knowledge was considered average, meaning that they had an average level of disaster awareness. They possessed an average understanding of disasters, volcanic eruptions, and the risks of carrying out activities in the disaster-prone tourism area. However, the practical knowledge of self-rescue during emergency response remained low. Cross tabulation suggested a low and directional correlation between disaster knowledge and the visitors' experiences in participating in disaster preparedness training or simulations. Keywords: disaster awareness, disaster knowledge, visitors, disaster-prone tourism area of mount merapi .